Development of a Web-Based Information System in Kebondowo Village - Heluy Tiana Rosa; Aji Priyambodo; Andreas Tigor Oktaga (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
This research aims to develop a web-based information system at the Kebondowo village office. This research was conducted by analyzing the extent to which the Kebondowo Village Office uses an effective information system. This system development uses PHP, HTML and MySQL programming languages with the waterfall model method with several stages, namely requirements analysis, design, development, testing, and maintenance. The results of the study can be concluded that the Kebondowo Village Information System that can support activities in Kebondowo Village to the community. The Kebondowo Village website has been designed and implemented to improve the quality of public services by presenting information about profiles, announcements, and village activity agendas. This initiative makes it easier for Kebondowo Village Officials to deliver information directly without intermediaries, as well as providing convenience for residents to access and receive accurate information, including about social assistance programs and other activity agendas in the village.